Conservation catalysts : how academics and researchers are advancing large landscape preservation - Levitt, James N.; Woodley, Stephen (Lincoln Institute of Land Policy, 2014)
"This multi-author volume explores large-landscape conservation projects catalyzed by colleges, universities, independent field stations, and research organizations around the world. These initiatives are grand-scale, cross-boundary, cross-sectoral, and cross-disciplinary efforts to protect working and wild landscapes and waterscapes in Australia, Canada, Chile, Colombia, Honduras, Kenya, Tanzania, Trinidad & Tobago, and the United States"--